2015
DOI: 10.1021/acs.bioconjchem.5b00630
|View full text |Cite
|
Sign up to set email alerts
|

Bioorthogonal Fluorophore Linked DFO—Technology Enabling Facile Chelator Quantification and Multimodal Imaging of Antibodies

Abstract: Herein we describe the development and application of a bioorthogonal fluorogenic chelate linker that can be used for facile creation of labeled imaging agents. The chelate linker is based on the trans-cyclooctene(TCO)-tetrazine(Tz) chemistry platform and incorporates deferoxamine (DFO) as a 89Zr PET tracer and a BODIPY fluorophore for multimodal imaging. The rapid (<3 min) ligation between mAb-TCO and Tz-BODIPY-DFO chelator is monitored using fluorescence and allows for determination of labeling completion. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
58
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 25 publications
2
58
0
Order By: Relevance
“…We have used a similar approach to quantify conjugation efficiency of fluorogenic BODIPY-DFO derivatives to antibodies. 44 The trifunctional trastuzumab conjugate 8 –trastuzumab was also utilized for the study of probe uptake in cells using fluorescence microscopy. We incubated BT474 cells (5 × 10 4 ) with 15 μ g of conjugate for 24 h and subsequently assessed cell uptake by fluorescence microscopy.…”
Section: Resultsmentioning
confidence: 99%
“…We have used a similar approach to quantify conjugation efficiency of fluorogenic BODIPY-DFO derivatives to antibodies. 44 The trifunctional trastuzumab conjugate 8 –trastuzumab was also utilized for the study of probe uptake in cells using fluorescence microscopy. We incubated BT474 cells (5 × 10 4 ) with 15 μ g of conjugate for 24 h and subsequently assessed cell uptake by fluorescence microscopy.…”
Section: Resultsmentioning
confidence: 99%
“… Hetero‐bifunctional SCF linkers for the fabrication of tumor‐targeting dual‐modality imaging probes, antibody–probe conjugates, through fluorogenic conjugation between an antibody and nuclear imaging moiety: a) conjugation of DFO, a 89 Zr PET tracer, with tz‐TCO by utilizing SCF4 as the bridging unit; b) conjugation of 2,2′‐[7‐(3‐amino‐1‐carboxypropyl)‐1,4,7‐triazonane‐1,4‐diyl]diacetic acid (NH 2 ‐NOTA), a 64Cu PET tracer, with acrylamide‐functionalized cetuximab (ct‐Acm) by utilizing SCF5 as the bridging unit …”
Section: Fluorogenic Bifunctional Linkersmentioning
confidence: 99%
“…In this respect, Weissleder et al reported fluorogenic conjugation between deferoxamine (DFO), a 89 Zr PET tracer,a nd transcyclooctene-functionalized trastuzumab (tz-TCO) by utilizing SCF4 as af luorogenic linker. [60] Notably,t he fluorogenic nature allows for the quantification of coupling efficiency. An onfluo-rescenti ntermediate, SCF4-DFO, was synthesized first through an amidation reaction.…”
Section: Hetero-bifunctional Scf Linkersmentioning
confidence: 99%
“…[1415] Subsequently, we designed and synthesized a Tb(III) complex that allows for covalent attachment of the CR emitting isotope 89 Zr, generating a Tb(III) complex with an intramolecular CR source (Scheme 2). …”
mentioning
confidence: 99%